Early intervention with oral mucosal barrier Protective agents in chronic oral graft-versus-host disease: a retrospective cohort study - Jianqiong Cao; Lijuan Ye; Xiao Li; Qiujin Song; Yanyan Chai (BMC, 2024)
Abstract Background Preventing the progression of chronic oral graft-versus-host disease (cGVHD) is essential for maintaining oral health, improving quality of life, minimizing functional impairment, reducing systemic complications, and addressing treatment challenges. Purpose To evaluate the effectiveness of early intervention with oral mucosal barrier protective agents in preventing the progression of cGVHD and its impact on oral health, quality of life, and treatment response. Methods This retrospective cohort study included 75 participants, with 34 in the non-oral mucosal barrier protective agent group and 41 in the oral mucosal barrier protective agent group. Baseline characteristics, oral mucosal health parameters, quality of life assessments, and curative effect data were collected and compared between the two study groups. Results The group receiving oral mucosal barrier protectants (n = 41) exhibited significantly lower severity of oral mucositis compared to the group without such protectants (n = 34) (2.12 ± 0.48 vs. 2.56 ± 0.63, P = 0.001) and the incidence of complications was significantly lower in the group receiving oral mucosal barrier protectants (P < 0.05). Additionally, the quality of life assessment showed marked improvements in somatization, emotional management, and social reintegration in the oral mucosal barrier protectant group compared to the group without these protectants (P < 0.05). Furthermore, the assessment of treatment efficacy revealed significantly higher rates of both complete and partial responses in the oral mucosal barrier protectant group, along with a notable reduction in disease progression compared to the group without these protectants (P < 0.001). Conclusion Early intervention with oral mucosal barrier protective agents was associated with improved oral health parameters, enhanced quality of life, and a more favorable treatment response in the context of cGVHD.